Who has influence in multistakeholder governance systems? Using the net-map method to analyze social networking in watershed management in northern Ghana - Schiffer, Eva; Hartwich, Frank; Monge, Mario (International Food Policy Research Institute, 2010)
As multistakeholder governance has emerged as an important feature in development, new governance structures that foster the participation of multiple stakeholders from the public sector, civil society, and the private sector have emerged in various fields, ranging from the management of natural resources to the provision of public services. To make such governance structures work, it is essential to understand how different stakeholders influence decisionmaking and what determines their influence. This paper uses Net-Map, an innovative participatory method, to analyze how networking influences decisionmaking in multistakeholder governance structures, using the case of the governance board of the White Volta River Basin in northern Ghana as an example. The method visualizes both the relations between all stakeholders in watershed management as perceived by the 17 members on the board and their influence on development outcomes. The study suggests that significant effects of social networking are at play beyond the formal lines of command and funding as stakeholders in watershed management make decisions. Stakeholders are more influential if they participate more prominently in information exchange and provide more advice to others. This counterbalances the overrepresentation of government actors on the board. Meanwhile some government organizations have a low level of influence, even though they are central in giving funding and command. These findings may be interesting for program leaders and policymakers in watershed management: when designing governance structures they need to take into account the importance of social networking to attain main objectives of watershed development; it is important to provide space that allows the exchange of information and advice among stakeholders. Meanwhile, policymakers and program leaders as well must consider overrepresentation of social network champions in multistakeholder governance structures and the limited capacity of government bodies in social networking. The paper serves to introduce not only the specific findings concerning this case study but also the participatory research method (Net-Map) that was used.